Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 59576 by maxmathsup by imad last updated on 12/May/19

let f(x) =∫       (dt/((x+t)(√(t^2 −x^2 ))))  1) determine a explicit form of f(x)  2) determine ∫     (dt/((x+2)(√(t^2 −4))))  and  ∫      (dt/((x+1)(√(t^2 −1))))

letf(x)=dt(x+t)t2x21)determineaexplicitformoff(x)2)determinedt(x+2)t24anddt(x+1)t21

Commented by tanmay last updated on 12/May/19

∫(dt/((t+2)(√(t^2 −4)))) and ∫(dt/((t+1)(√(t^2 −1))))  ∫(dt/((t+a)(√(t^2 −a^2 ))))  k=(1/(t+a))  t+a=(1/k)→dt=((−dk)/k^2 )  ∫(k/(√(((1/k))((1/k)−2a))))×((−dk)/k^2 )  ∫((−dk)/(k(√((1−2ak)/k^2 ))))   p^2 =1−2ak   →2pdp=−2adk  ∫((pdp)/(a×p))  (1/a)×p+c  =((√(1−2ak))/a)+c  =((√(1−((2a)/(t+a)) ))/a)+c  now put a=2    ((√(1−(4/(t+2))))/2)+c....(ans for Qno 1)  now put a=1  ((√(1−(2/(t+1))))/1)+c....(ans for Qno 2)

dt(t+2)t24anddt(t+1)t21dt(t+a)t2a2k=1t+at+a=1kdt=dkk2k(1k)(1k2a)×dkk2dkk12akk2p2=12ak2pdp=2adkpdpa×p1a×p+c=12aka+c=12at+aa+cnowputa=214t+22+c....(ansforQno1)nowputa=112t+11+c....(ansforQno2)

Commented by maxmathsup by imad last updated on 12/May/19

2)the Q.is determine ∫  (dt/((t+2)(√(t^2 −4))))  and ∫  (dt/((t+1)(√(t^2 −1))))

2)theQ.isdeterminedt(t+2)t24anddt(t+1)t21

Commented by maxmathsup by imad last updated on 14/May/19

changement t =x ch(u) give f(x)=∫  ((xsh(u))/((x+xch(u))∣x∣sh(u))) du  =ξ(x) ∫   (du/(x(1+ch(u)))) =((ξ(x))/x) ∫   (du/(1+((e^u  +e^(−u) )/2))) =((2ξ(x))/x) ∫   (du/(2 +e^u  +e^(−u) ))  =_(e^u =α) ((2ξ(x))/x) ∫   (1/(2 +α +α^(−1) )) (dα/α) =((2ξ(x))/x) ∫    (dα/(2α +α^2  +1))  =((2ξ(x))/x) ∫  (dα/((α+1)^2 )) =−((2ξ(x))/x) (1/(α+1)) +c =−(2/x)ξ(x) (1/(e^u  +1))  but  u =argch((t/x)) =ln((t/x)+(√((t^2 /x^2 )−1))) ⇒e^u  =(t/x)+(√((t^2 /x^2 )−1)) ⇒  f(x) =−(2/x)ξ(x) (1/((t/x)+((√(t^2 −x^2 ))/(∣x∣)))) +c =−((2ξ(x))/(t +ξ(x)(√(t^2 −x^2 )))) +c  with  ξ(x) =1 if x>0  and ξ(x)=−1 if x<0 so   f(x) =((−2)/(t+(√(t^2 −x^2 )))) +c  if x>0  f(x)=(2/(t−(√(t^2 −x^2 ))))+c if x<0

changementt=xch(u)givef(x)=xsh(u)(x+xch(u))xsh(u)du=ξ(x)dux(1+ch(u))=ξ(x)xdu1+eu+eu2=2ξ(x)xdu2+eu+eu=eu=α2ξ(x)x12+α+α1dαα=2ξ(x)xdα2α+α2+1=2ξ(x)xdα(α+1)2=2ξ(x)x1α+1+c=2xξ(x)1eu+1butu=argch(tx)=ln(tx+t2x21)eu=tx+t2x21f(x)=2xξ(x)1tx+t2x2x+c=2ξ(x)t+ξ(x)t2x2+cwithξ(x)=1ifx>0andξ(x)=1ifx<0sof(x)=2t+t2x2+cifx>0f(x)=2tt2x2+cifx<0

Commented by maxmathsup by imad last updated on 14/May/19

2) ∫   (dt/((t+2)(√(t^2 −4)))) =f(2) =((−2)/(t +(√(t^2 −4)))) +c  ∫   (dt/((t+1)(√(t^2 −1)))) =f(1) =((−2)/(t +(√(t^2 −1)))) +c

2)dt(t+2)t24=f(2)=2t+t24+cdt(t+1)t21=f(1)=2t+t21+c

Terms of Service

Privacy Policy

Contact: info@tinkutara.com